2022
DOI: 10.3390/cimb44040097
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Folic Acid Mimics Folate Deficiency in Human Lymphocytes

Abstract: Food fortification with synthetic folic acid (FA), along with supplementation, results in a marked increase in the population total of serum folates and unmetabolized folic acid (UMFA). Despite the success in reducing neural tube defects at birth in the intended target population (women of childbearing age), the potential deleterious effects of chronically high levels of UMFA in susceptible segments of the population require further investigation. In this study, we examine the effects of FA concentrations, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Folate’s role in nucleotide synthesis, DNA repair, and genomic stability is well established. Several studies evaluated the impact of folate deficiency and adequacy on MNi, NPB and NBUD formation in human lymphocytes in vitro [ 41 , 56 , 57 , 58 , 59 ]. Based on the current body of evidence, the prevailing paradigm suggests that folate deficiency is deleterious, while a high folate intake is beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Folate’s role in nucleotide synthesis, DNA repair, and genomic stability is well established. Several studies evaluated the impact of folate deficiency and adequacy on MNi, NPB and NBUD formation in human lymphocytes in vitro [ 41 , 56 , 57 , 58 , 59 ]. Based on the current body of evidence, the prevailing paradigm suggests that folate deficiency is deleterious, while a high folate intake is beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many in the field inadvertently use the term folate to describe both natural and synthetic forms, potentially leading to misinterpretation of results. We previously demonstrated that excess folic acid could mimic folate deficiency in a human lymphoblastoid cell line (LCL) [ 41 ]. To date, the effects of excessive folic acid intake on cytome biomarkers in human lymphocytes in vivo has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that excess folic acid can mimic folate deficiency in a human lymphoblastoid cell line by similarly impacting genomic damage, global methylation, and expression of DNA repair genes [41]. Others reported complementary findings in C. elegans and mouse models where both FA deficiency and excess supplementation led to deleterious effects [42][43][44].…”
Section: Introductionmentioning
confidence: 95%